2019
DOI: 10.1091/mbc.e18-12-0791
|View full text |Cite
|
Sign up to set email alerts
|

Drosophila p53 directs nonapoptotic programs in postmitotic tissue

Abstract: TP53 is the most frequently mutated gene in human cancers, and despite intensive research efforts, genome-scale studies of p53 function in whole animal models are rare. The need for such in vivo studies is underscored by recent challenges to established paradigms, indicating that unappreciated p53 functions contribute to cancer prevention. Here we leveraged the Drosophila system to interrogate p53 function in a postmitotic context. In the developing embryo, p53 robustly activates important apoptotic genes in r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
15
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 101 publications
(116 reference statements)
4
15
0
Order By: Relevance
“…We did not see a significant difference in the proportion of dead cells in overexpression of p53 WT or p53 DN conditions compared to control (Supp. Fig.5B) consistent with recent work suggesting a non-canonical, non-apoptotic role for p53 in the Drosophila head 51 .…”
Section: Polyploidy Accumulation In Neurons Is P53-independentsupporting
confidence: 92%
See 1 more Smart Citation
“…We did not see a significant difference in the proportion of dead cells in overexpression of p53 WT or p53 DN conditions compared to control (Supp. Fig.5B) consistent with recent work suggesting a non-canonical, non-apoptotic role for p53 in the Drosophila head 51 .…”
Section: Polyploidy Accumulation In Neurons Is P53-independentsupporting
confidence: 92%
“…However the most significantly downregulated GO terms in the OL To further understand the DNA damage and cell cycle signatures observed with age, we looked at the change in expression of specific genes involved in the DNA damage response and the cell cycle ( Fig.5F). Recent work has identified a specific transcriptional response to induced DNA damage in the head that involved a non-canonical role for tumor suppressor protein p53 51 . This signature was termed head Radiation Induced p53-Dependent or hRIPD.…”
Section: Dna Damage Accumulates With Age In the Optic Lobesmentioning
confidence: 99%
“…Consistent with recent reports showing Dmp53 binding to egr locus [32], chromatin immunoprecipitation (ChIP) assays showed that Dmp53 binds to egr and reaper predicted binding sites with similar efficiency ( Figure 3K). Altogether, these results are consistent with Dmp53-activating egr gene expression through a conserved p53 binding site in egr promoter region.…”
Section: Dmp53 Target Genes Are Upregulated Upon Growth Stresssupporting
confidence: 91%
“…Besides its role in apoptosis, Drosophila p53 is known to have multiple non-apoptotic roles including a delay of larval development in response to IR damage [ 19 ], stimulation of Apoptosis-induced-Proliferation in a manner that is independent of its apoptosis-inducing function [ 31 ], reprogramming cellular metabolism during cell competition [ 32 ], and restraining transposon mobility in the germline [ 33 ]. A recent study found that in post-mitotic cells of the adult Drosophila head, p53 regulates transcription programs for DNA repair, proteolysis and metabolism in response to IR [ 34 ]. We do not know what aspect of p53 functions is responsible for culling mwh cells nor do we know when in development this culling occurs because we cannot monitor mwh except in wings near the end of development.…”
Section: Discussionmentioning
confidence: 99%